Commercial tobacco and indigenous peoples: a stock take on Framework Convention on Tobacco Control progress. Issue 5 (3rd August 2018) - Maddox, Raglan; Waa, Andrew; Lee, Kelley; Nez Henderson, Patricia; Blais, Genevieve; Reading, Jeff; Lovett, Raymond
Abstract : Background: The health status and needs of indigenous populations of Australia, Canada and New Zealand are often compared because of the shared experience of colonisation. One enduring impact has been a disproportionately high rate of commercial tobacco use compared with non-indigenous populations. All three countries have ratified the WHO Framework Convention on Tobacco Control (FCTC), which acknowledges the harm caused to indigenous peoples by tobacco. Aim and objectives: We evaluated and compared reporting on FCTC progress related to indigenous peoples by Australia, Canada and New Zealand as States Parties. The critiqued data included disparities in smoking prevalence between indigenous and non-indigenous peoples; extent of indigenous participation in tobacco control development, implementation and evaluation; and what indigenous commercial tobacco reduction interventions were delivered and evaluated. Data sources: We searched FCTC: (1) Global Progress Reports for information regarding indigenous peoples in Australia, Canada and New Zealand; and (2) country-specific reports from Australia, Canada and New Zealand between 2007 and 2016. Study selection: Two of the authors independently reviewed the FCTC Global and respective Country Reports, identifying where indigenous search terms appeared. Data extraction: All data associated with the identified search terms were extracted, and content analysis was applied. Results: It is difficult to determine if or what progress has been made to reduce commercial tobacco use by the three States Parties as part of their commitments under FCTC reporting systems. There is some evidence that progress is being made towards reducing indigenous commercial tobacco use, including the implementation of indigenous-focused initiatives. However, there are significant gaps and inconsistencies in reporting. Strengthening FCTC reporting instruments to include standardised indigenous-specific data will help to realise the FCTC Guiding Principles by holding States Parties to account and building momentum for reducing the high prevalence of commercial tobacco use among indigenous peoples.